Analisis Keberlanjutan Usaha Ternak Sapi Perah Di Kecamatan Krucil Kabupaten Probolinggo - Camal Adi Maskur; Dian Afikasari; Mohamad Ervandi (Jurnal Sains Ternak Tropis, 2026)
Dairy cattle farming contributes to the Indonesian economy by improving food security. Probolinggo Regency is one of the regions with significant potential for the development of dairy farming. One of the districts in Probolinggo Regency with a considerable dairy cattle population is Krucil District. This study aimed to identify the social, economic, infrastructure and technology, as well as legal and institutional dimensions.The research employed qualitative descriptive and explanatory methods using a survey approach. The results of the study on the sustainability of dairy cattle farming showed that, in the social dimension, the level of education of farmers was categorized as low and the age of farmers tended to be advanced. However, other aspects such as time allocation for livestock activities, community access and perceptions, as well as social roles and patterns of community relationships in dairy farming activities were categorized as high. These conditions can encourage participation and support the continuity of dairy farming enterprises.Indicators in the economic dimension were generally in the moderate category, indicating that dairy farming businesses have not yet been optimized and therefore have not created a highly competitive agribusiness system. Infrastructure and technology play an important role in supporting dairy cattle farming, as reflected by the relatively moderate score in the infrastructure and technology dimension. The legal and institutional aspects showed an average moderate value, indicating that legal and institutional functions have not been fully optimized. Nevertheless, the existence of farmer groups and the involvement of farmers play an important role in supporting the progress of dairy farming enterprises.Usaha peternakan sapi perah memberikan kontribusi bagi perekonomian di Indonesia dalam meningkatkan ketahanan pangan. Kabupaten Probolinggo merupakan salah satu kabupaten yang memiliki potensi besar dalam pengembangan usaha ternak perah. Salah satu kecamatan di kabupaten Probolinggo yang memiliki populasi ternak sapi perah yaitu kecamatan Krucil. Penelitian ini bertujuan mengidentifikasi dimensi sosial, ekonomi, infrastruktur dan teknologi serta hukum dan kelembagaan. Metode penelitian ini menggunakan deskriptif dan eksplanatori kualitatif dengan menggunakan metode survey. Hasil penelitian mengenai keberlangsungan usaha ternak sapi perah menunjukan hasil Pada dimensi sosial menunjukkan tingkat pendidikan dalam kategori rendah dan usia peternak dalam kategori lanjut. Akan tetapi dimensi lain yang menyangkut alokasi waktu untuk usaha ternak, akses dan pandangan masyarakat, peran dan pola hubungan masyarakat dalam kegiatan usaha sapi perah terkategori tinggi, hal ini dapat mendorong partisipasi dan terus berlansungnya usaha peternakan.Indikator dalam dimensi ekonomi rata – rata masuk dalam kategori sedang, artinya usaha ternak sapi perah belum optimal sehingga belum menciptakan sistem agribisnis yang mempunyai daya saing yang tinggi. Infrastruktur dan teknologi mempunyai peran penting dalam menunjang usaha ternak sapi perah. Hal ini di tunjukan pada hasil dimensi infrastruktur dan teknologi yang relatif sedang. Aspek hukum dan kelembagaan menunjukan nilai rata-rata sedang artinya fungsi hukum dan kelembagan belum maksimal. Akantetapi indikator keberadaan kelompok tani dan keterlibatan peternak memegang peran penting dalam menunjang kemajuan usaha.